My unfair lady ebook - Kennedy, Kathryne (2009)
A Library Journal Editor's Pick! "Those who relish unconventional, outspoken heroines; dark, cynical heroes; and a plot spiced with a soupçon of danger ...should find Kennedy's Victorian romance version of My Fair Lady quite entertaining."—Booklist Summer Wine Lee peeked through the drapery covering the second-story window of their rented London town house, hoping to catch a glimpse of the man she intended to hire to change her life forever. The impoverished Duke of Monchester despises the rich Americans who flock to London, seeking to buy their way into the ranks of the British peerage. So when railroad heiress Summer Wine Lee offers him a king's ransom if he'll teach her to become a proper lady, he's prepared to rebuff her. But when he meets the petite beauty with the knife in her boot, it's not her fortune he finds impossible to resist. Frontier-bred Summer Wine Lee has no interest in winning over London society—it's the New York bluebloods and her future mother-in-law she's determined to impress. She knows the cost of smoothing her rough-and-tumble frontier edges will be high. But she never imagined it might cost her heart. A delightful combination of the Wild West and English society, My Unfair Lady, is an unusual Victorian historical romance. Fans of Jennifer Ashley, Lorraine Heath, Madeline Hunter, and Christi Caldwell will be enraptured by this tale of an American heiress, a British Duke, and finding love and acceptance just the way you are.